Agonistic anti‐CD27 antibody ameliorates EAE by suppressing IL‐17 production. Issue 10 (15th August 2022) - Vogel, Isabel; Acolty, Valerie; Keler, Tibor; Goriely, Stanislas; Leo, Oberdan; Moser, Muriel
ABSTRACT: CD27/CD70 costimulation enhances T‐cell survival, memory formation and Th1‐cell differentiation and effector function. In addition to promoting Th1 responses, CD27 signaling has been shown to exert a negative regulatory role on IL‐17 production, resulting in increased sensitivity of CD27 KO mice to EAE. By inducing EAE in full CD27 KO mice, and in a novel, T‐cell specific CD27 KO mouse strain (CD4‐Cre x CD27 flox/flox ), we demonstrate herein that CD27 engagement by its natural ligand (CD70) suppresses IL‐17 production in a cell autonomous fashion. We further show that CD27 engagement by an agonistic antibody given after EAE induction or at symptom onset similarly suppresses IL‐17 production by activated CD4 + T cells infiltrating the inflamed CNS while IFN‐γ production was unaffected, leading to an amelioration of inflammatory‐related symptoms. These findings propose CD27 costimulation as a potential candidate for therapeutic manipulation to treat autoimmune and autoinflammatory diseases characterized by excessive IL‐17 production. Abstract : T‐cell specific deletion of CD27 results in increased IL‐17 production and exacerbated EAE. Treating mice with an agonistic anti‐CD27 antibody after EAE induction or after onset of clinical disease signs results in reduced IL‐17 production and amelioration of EAE disease scores.